(3GdcGajs - (3GdMGce GdeQhRj , eMeO Hf eMeO Hf CMeO GdeQhRj GdSdej GdHdNj, CHh GdaVd GdMGce GdTgjO,J (B334 (3g` s
(3ChdgG (B:s
(3Chd cJGH GdSjQ GdUZjQ s
(3GdfSNI HgG MhGTs
(3Vefg eYGfi cJGH GdEeGe eMeO Hf GdMSf GdTjHGfis
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B19 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B185s
Keywords: (3Gdabg GdMfajs